Leading in Entrepreneurial Universities: Do Demographics Display Different Commitments? - Fatimah, Fatimah; Sarbaini, Sarbaini; Arisanty, Deasy (Frontiers in Education, 2022)
For the excellence of universities as instructional institutions, lecturers' dedication has been extensively acknowledged as a productive trajectory. Since public university in Indonesia remains the most influential place leading to the growth of a nation, it needs dedicated lecturers as strategic partners. This study analyzes the contemporary dedication of lecturers by looking at affective, continuance, or normative dimensions and assesses whether or not there is any major variance between the chosen demographics over organizational dedication questions. The information had been received from 500 full-time lecturers serving public universities in Indonesia. The findings indicate that most lecturers possess continuance commitment (CC), for they calculate the prices and advantages associated with no longer serving the university. Further, when better options are available, they will leave their universities. From the selected demographic variables examined, only the level of education and length of service significantly affect the commitment of university teachers. This study finds that the lecturers and the universities are engaged in a reciprocal relationship. When lecturers are treated professionally, they respond with more outstanding commitment as they discover them as a necessary section of the organization. Consequently, universities rely on dedicated lecturers to create and sustain a competitive advantage in maintaining world ranking.